A Mid-1450s Anonymous Exhortatio pro cruce assumenda contra infideles et paganos (Melk, Stiftsbibliothek, 1799) - Portnych, Valentin Leonidovič (Medieval sermon studies, 2025)
The following article comprises an introduction to, and edition of a preaching text titled Exhortatio pro cruce assumenda contra infideles et paganos, an exhortation for taking the cross against the infidels and heathens. This text has been found in a mid-fifteenth century manuscript currently preserved and possibly produced in the Benedictine abbey of Melk (modern-day Austria), Nr. 1799. The text itself is likely to have been composed under the pontificate of Callixtus III (1455-58), since it mentions ‘two pontiffs and their bulls’, very probably the bull Ad summi pontificatus apicem by Callixtus III (1455), which quotes the complete text of the bull Etsi ecclesia Christi by Nicholas V (1453) amending it. There is strong evidence that the treatise De predicatione crucis (On the Preaching of the Cross) by Humbert of Romans, c. 1266-68, or an unknown intermediary source quoting it, is widely used in the exhortation.